Geniposide and Chlorogenic Acid Combination Improves Non-Alcoholic Fatty Liver Disease Involving the Potent Suppression of Elevated Hepatic SCD-1 - Chen, Cheng; Xin, Xin; Liu, Qian; Tian, Hua-Jie; Peng, Jing-Hua; Zhao, Yu; Hu, Yi-Yang; Feng, Qin (Frontiers in Pharmacology, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD), characterized by the excessive accumulation of hepatic triglycerides (TGs), has become a worldwide chronic liver disease. But efficient therapy keeps unsettled. Our previous works show that Geniposide and Chlorogenic acid combination (namely the GC combination), two active chemical components combined with a unique ratio (67,16:1), presents beneficial effects on high-fat diet-induced NAFLD rodent models. Notably, microarray highlighted the more than 5-fold down-regulated SCD-1 gene in the GC combination group. SCD-1 is an essential lipogenic protein for monounsaturated fatty acids' biosynthesis and serves as a key regulatory enzyme in the last stage of hepatic de novo lipogenesis (DNL). Methods: NAFLD mice model was fed with 16 weeks high-fat diet. The pharmacological effects, primarily on hepatic TG, TC, FFA, and liver enzymes, et al. of the GC combination and two individual components were evaluated. Furthermore, hepatic SCD-1 expression was quantified with qRT-PCR, immunoblotting, and immunohistochemistry. Finally, the lentivirus-mediated over-expressed cell was carried out to confirm the GC combination's influence on SCD-1. Results: The GC combination could significantly reduce hepatic TG, TC, and FFA in NAFLD rodents. Notably, the GC combination presented synergetic therapeutic effects, compared with two components, on normalizing murine hepatic lipid deposition and disordered liver enzymes (ALT and AST). Meanwhile, the robust SCD-1 induction induced by HFD and FFA in rodents and ALM-12 cells was dramatically blunted, and this potent suppression was recapitulated in lentivirus-mediated SCD-1 over-expressed cells. Conclusion: Taken together, our data prove that the GC combination shows a substantial and synergetic anti-lipogenesis effect in treating NAFLD, and these amelioration effects are highly associated with the potent suppressed hepatic SCD-1 and an impaired DNL process.